2015
DOI: 10.1055/s-0035-1559775
|View full text |Cite
|
Sign up to set email alerts
|

Positive Predictive Value of Abdominal Sonography in the Diagnosis of Ischemic Colitis

Abstract: In an appropriate clinical setting, ultrasound has a high positive predictive value for the diagnosis of ischemic colitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Ultrasound is a noninvasive imaging-based examination and is sensitive to the early structural changes in colonic walls caused by ischemia. Lopez et al [41] found that the positive predictive value (PPV) of abdominal ultrasound in detection of IC was 87.5%. A retrospective study reported that the predictive model consisting of sonographic features and clinical findings could accurately predict the outcomes of IC affliction and distinguish properly between patients with mild and severe cases of IC [42].…”
Section: Imaging Examinationmentioning
confidence: 99%
“…Ultrasound is a noninvasive imaging-based examination and is sensitive to the early structural changes in colonic walls caused by ischemia. Lopez et al [41] found that the positive predictive value (PPV) of abdominal ultrasound in detection of IC was 87.5%. A retrospective study reported that the predictive model consisting of sonographic features and clinical findings could accurately predict the outcomes of IC affliction and distinguish properly between patients with mild and severe cases of IC [42].…”
Section: Imaging Examinationmentioning
confidence: 99%
“…The late diagnosis of colonic ischemia is explained by the low degree of suspicion despite new imagistic methods [16]. Ultrasound is considered a valid method of diagnosis of colonic ischemia in the absence of colonoscopy [16].…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound is considered a valid method of diagnosis of colonic ischemia in the absence of colonoscopy [16]. Angiography and nuclear medicine (In-111 label leukocyte scans) were rarely helpful in diagnosis of ischemic colitis.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasonography, a non-invasive and readily available test, has the ability to detect mural thickening of the colon and suggests this pathology in patients with abdominal pain. Therefore, parietal thickening of a segment of the large bowel with a length of more than 10 cm, in a symptomatic patient with advanced age (>50 years), is a strong indication for IC ( 60 ). According to Lopez et al, abdominal sonography has a high positive predictive value in detecting IC (PPV 87.5%).…”
Section: Diagnostic Evaluationmentioning
confidence: 99%
“…However, ultrasonography cannot detect intestinal pneumatosis, which is detectable by the CT imaging. Moreover, CT is preferable than ultrasound in identifying cases of IC after AAA repair, since the colonic wall is often not thickened in these cases and the diagnosis is made in the absence of contrast enhancement of the diseased colon ( 60 ).…”
Section: Diagnostic Evaluationmentioning
confidence: 99%